Important determinants of newborn health. Issue 1 (February 2015) - McPeak, Katie E.; Sandrock, Deborah; Spector, Nancy D.; Pattishall, Amy E.
<x xml:space="preserve">Abstract</x> Purpose of review The present article addresses recent research related to three important determinants of newborn health: postpartum depression, teenage parents and their offspring, and breast-feeding. Recent findings Postpartum depression can impact the entire family unit, and fathers may be affected more than previously recognized. Teenage mothers and their infants are at risk of a number of poor physical and mental health outcomes. New research continues to support the benefits of breast-feeding infants, and hospitals have adopted policies to improve breast-feeding rates. Summary Recognizing both maternal and paternal depression during outpatient visits is key to family well-being, as well as to infant development and attachment. Pediatric providers should address the unique emotional, socioeconomic, educational, and health needs of teen mothers. Hospital implementation of evidence-based policies may increase the number of mothers who are successful in establishing breast-feeding, and pediatric healthcare providers should be prepared to support mothers of breast-feeding infants.